2009
DOI: 10.1111/j.1440-1746.2009.05864.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatitis B virus reverse transcriptase sequences in Chinese treatment naive patients

Abstract: Primarily antiviral resistance related mutant strains do exist in treatment naïve patients. Without antiviral pressure, HBV strains evolved at a normal speed. In depth sequence analysis implied that viral replication might be correlated with its variability, which needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 21 publications
4
44
1
Order By: Relevance
“…We recently demonstrated the usefulness of ultra-deep sequencing technology to unveil the massive genetic heterogeneity of hepatitis C virus (HCV) in association with treatment response to antiviral therapy [19]. On the other hand, there are a few published studies in which this technology was used to characterize genetic HBV sequence variations [20][22]. Margeridon-Thermet et al reported that the 454 Life Science GS20 sequencing platform provided higher sensitivity for detecting drug-resistant HBV mutations in the serum of patients treated with nucleoside and nucleotide reverse-transcriptase inhibitors [20].…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated the usefulness of ultra-deep sequencing technology to unveil the massive genetic heterogeneity of hepatitis C virus (HCV) in association with treatment response to antiviral therapy [19]. On the other hand, there are a few published studies in which this technology was used to characterize genetic HBV sequence variations [20][22]. Margeridon-Thermet et al reported that the 454 Life Science GS20 sequencing platform provided higher sensitivity for detecting drug-resistant HBV mutations in the serum of patients treated with nucleoside and nucleotide reverse-transcriptase inhibitors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the results also suggested that NA treatment is the major selecting factor of primary drug-resistant mutations and that NA treatment promotes putative NAr mutations (Li et al, 2012). Moreover, several previous studies showed that primary NAr mutations occur in patients with no history of NA treatment (Han et al, 2009;Kobashi et al, 2009;Pastor et al, 2009). Recently, another paper also reported that HBV resistance mutations were identified in 5 % of treatment-naïve patients by using INNO-LiPA (Fujirebio) line probe analysis (Mirandola et al, 2011).…”
mentioning
confidence: 99%
“…Recent reports showing the existence of antiviral resistance strains in treatment-naïve hepatitis B individuals alert the need for baseline monitoring of antiviral resistance mutants [19][20][21] . Hence in the present study we attempted to identify and analyze the HBVrt amino acid substitutions capable of conferring resistance to antivirals in treatment-naïve HBV-infected individuals from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%